Pengaruh Persepsi Wajib Pajak Orang Pribadi Atas Pelaksanaan Self Assessment System, Keadilan, Dan Teknologi Perpajakan Terhadap Tindakan Tax Evasion - Naluri April Leana; Nur Kholis (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
The intention of the researcher to conduct this research is to examine and demonstrate the perception of individual taxpayers (WPOP) against Self assessment system, Justice and Technology actions Tax Evasion. population sample is individual taxpayers who live in district as many as 100 respondents by distributing questionnaires via googleform for data collection and random sampling as the research sample method as well as multiple linear regression as the data analysis method for technical processing assisted using SPSS version 25Then the results of hypothesis testing for each of these variables include the self-assessment system, justice and tax technology simultaneously have a negative effect on tax evasion measures. Keywords: Taxpayer Perception, Self Assessment System, Justice, Tax Technology, Tax Evasion